Capacity building of posyandu cadres through education and training in stunting prevention - Millati, Rida; Setyawati, Ari; Aris Tyarini, Indrawati; Daiyah, Isrowiyatun (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Increasing the capacity of Posyandu cadres is a strategic step in efforts to prevent stunting at the community level. The Community Service Program (PkM) aims to improve the knowledge and skills of Posyandu cadres in preventing stunting through education and training. The methods used include providing interactive materials, simulations, and field practices on risk factors, nutritional parenting, and early detection of stunting. The program participants are Posyandu cadres in the assisted areas with 30 people. The evaluation results showed a significant improvement in the knowledge and skills of cadres, which was measured through pre-test and post-test. In addition, cadres can apply the knowledge gained in Posyandu activities, such as educating mothers under five years old, detecting stunting risks, and developing simple intervention programs in the community. In conclusion, practice-based education and training effectively increase Posyandu cadres' capacity for stunting prevention. This program is expected to contribute to reducing the prevalence of stunting in the assisted areas